2010
DOI: 10.2353/ajpath.2010.090432
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Inhibits Wound Healing in Male Mice via Estrogen Receptor-α

Abstract: Although estrogens have long been known to accelerate healing in females, their roles in males remain to be established. To address this, we have investigated the influence of 17␤-estradiol on acute wound repair in castrated male mice. We report that sustained exposure to estrogen markedly delays wound re-epithelialization. Our use of hairless mice revealed this response to be largely independent of hair follicle cycling, whereas other studies demonstrated that estrogen minimally influences wound inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The low levels of STAT3 bound to the miR‐7 promoter, in this study, may therefore have an alternative role to transcriptional transactivation of miR‐7; a mechanism for which should be elucidated in future research. Also of interest would be defining the active ER involved, as both ERα and ERβ were identified to associate with the miR‐7 promoter; however, each was reported to have different roles in cell function and wound healing (Gilliver et al ., 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The low levels of STAT3 bound to the miR‐7 promoter, in this study, may therefore have an alternative role to transcriptional transactivation of miR‐7; a mechanism for which should be elucidated in future research. Also of interest would be defining the active ER involved, as both ERα and ERβ were identified to associate with the miR‐7 promoter; however, each was reported to have different roles in cell function and wound healing (Gilliver et al ., 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in male hyperlipidemic analbuminemic rats, estradiol supplementation accelerates the development of renal disease by promoting proteinuria and GSI (11). Supplementation of estradiol in castrated male MF-1 mice slows and delays epithelialization in wound healing (7). Thus, estrogens appear to exert opposing effects in diabetic males and females; however, the mechanisms by which these opposing effects are mediated remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gilliver et al. (39) showed that oestradiol did not influence the expression of MMP‐2 in isolated macrophages but showed its in vivo effects on MMP release, which is probably regulated indirectly. Similarly, we showed that both tested ER agonists increased MMP‐2 and MMP‐9 expression but not activity in HUVECs in vitro .…”
Section: Discussionmentioning
confidence: 99%